Analisis Penentuan Strategi Dalam Lingkungan Bisnis Yang Kompetitif Studi Kasus Pada PT. PELINDO IV (Persero) - lapod, jhon (Universitas Sam Ratulangi, 2016)
Economic globalization, free trade world, the ASEAN Economic Community (AEC), marine highway program, changes in consumer behavior, causing important for PT.PELINDO IV to examine best strategy practice in facing such a situation in order to be competitive and sustainable. The results showed that : based on the SWOT diagram mapping, PT Pelindo IV is in first quadrant. This position indicates a strong company and potentially, recommendations strategy that given is progressive, which mean the company in good condition and steady so it is possible to continue to expand, enlarge growth and achieve maximum growthKeywords: Strategy, SWOT, PT. Pelindo IV Limited